Diseases of Aeschynomene species - Sonoda, RM; Lenné, Jillian M. (1986)
Diseases of Aeschynomene spp. observed in forage evaluation trials in South America and Florida, U.S.A. are described and discussed. Newly discovered diseases include Polythrincium sp. leaf blotch, Calonectria sp. dieback, and Rhizoctonia solani Kuhn foliar blight. Diseases previously reported from native populations of Aeschynomene spp. and those reported from forage evaluation trials from other areas of the world are reviewed. Most current testing of Aeschynomene spp. is conducted with plant materials with a narrow genetic base. There is a need to collect a wider spectrum of Aeschynomene germplasm for forage characteristics as well as disease resistance.